Apply with Caution: Introducing UK-Style In-work Support in Germany - Peter Haan; Michał Myck (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Estimates of labour supply effects of recent UK reforms in the area of direct taxes and benefits show that policy can have significant influence on the level of employment. We confirm this in a simulation of in-work support system introduced into the German tax and benefit system. Our simulation results suggest that introducing in-work Tax Credits in Germany would increase employment of single individuals by over 100,000 but it would result in a reduction of labour supply among individuals living in couples by about 70,000. We find that Tax Credits would result in significant reductions of labour supply both among women and men in two earner couples. The result found for men is especially important as it is markedly different from all results found for the UK, where the overall response among men has always been found positive. Our estimation results call for a high degree of caution as far as ?importing? UK-style Tax Credits to Germany is concerned. In-work support based on family income would reinforce the existing work disincentives for secondary earners through joint income taxations, reducing the employment levels of both men and women living in couples.
Keywords: J22; H31; C52; C25; 330; tax-benefit system; in-work benefits; microsimulation; household labour supply; Einkommensteuer; Steuerbegünstigung; Arbeitsangebot; Großbritannien; Deutschland